The Power of Share Wave Elastography in Evaluating Portal Hypertension Signs in Children - Gülcü Taşkın, Didem; Cingöz, Mehmet; Ayyıldız Civan, Hasret; Beşer, Ömer Faruk; Adaletli, İbrahim and Cullu Cokugras, Fugen and Erkan, Tülay and Kutlu, Tufan (Cerrahpaşa Medical Journal, 2023)
Objective: We wanted to investigate the value of spleen elastography and liver elastography values measured by shear wave elastography and some parameters such as spleen size and spleen ratio in detecting the presence and grade of esophageal varices. Methods: The patient group included 43 patients diagnosed with portal hypertension and 63 healthy children. Spleen elastography and liver elastography were evaluated by shear wave elastography in patients who had screening gastroscopy for esophageal varices, and these patients were compared with healthy controls. Results: Both the liver elastography and spleen elastography values were significantly higher in portal hypertension patients than controls. The mean liver elastography and spleen elastography values were higher in the variceal hemorrhage group than in the varices non-hemorrhage group. The spleen ratio measured by ultrasonography and spleen elastography values were weakly correlated, while the mean liver elastography and spleen elastography values were higher in the esophageal varices group than in the non-varices group. The spleen elastography values and the liver elastography values are both higher in the presence of esophageal varices. For spleen elastography values of >30 kPa was the cutoff value for the detection of the esophageal varices. The spleen elastography values of >37 kPa was the cutoff for the detection of the esophageal varices hemorrhage. There is no significant correlation with the esophageal varices grade. Conclusion: We realized that the liver and spleen elastography values are changing with the presence of portal hypertension, esophageal varices, and variceal hemorrhage. But we could not find a significant correlation with the esophageal varices grade and liver elastography or spleen elastography values. Further studies are needed to determine the cutoff points for spleen elastography to indicate hemorrhage. Cite this article as: Gülcü Taşkın D, Cingöz M, Ayyıldız Civan H, et al. The power of share wave elastography in evaluating portal hypertension signs in children. Cerrahpaşa Med J. 2023;47(2):191-196.